Biodegradable biliary stents: is it time for a larger application in patients with benign biliary strictures?. Issue 127 (June 2020) - Mauri, Giovanni; Pescatori, Lorenzo; Sconfienza, Luca Maria
Highlights: Biodegradable biliary stents (BDBS) are safe in treating benign biliary strictures. Implant of BDBS has been validated in large multicentric studies. BDBS achieve good results with a low number of hospital admissions. BDBS should be wider used in treating patients with benign biliary stenosis.